Réponses

2013-12-28T23:10:55+01:00
Bonsoir

1) 9x² = 1
9x² - 1 = 0
(3x - 1)(3x + 1) = 0
3x - 1 = 0  ou   3x + 1 = 0
3x = 1       ou     3x = -1
x = 1/3      ou     x = -1/3

S = {1/3 ; -1/3}


2) 5x + 2/4 - 2x = 7/2 (3x - 5)
5x + 1/2 - 2x = (21/2)x - 35/2
5x - 2x - (21/2)x = -35/2 - 1/2
3x - (21/2)x = -36/2
(6/2)x - (21/2)x = -36
6x - 21x = -36
-15x = -36
x = -36/(-15)
x = 12/5

S = {12/5}


3) 
3 (4x - 6) + 2 (x + 10) > 3 (x - 3)
12x - 18 + 2x + 20 > 3x - 9
12x + 2x - 3x > -9 + 18 - 20
11x > -11
x > -11/11
x > -1

S = ]-1 ; +infini[
merci beaucoup ! j'adore cette application '-'
Avec plaisir :)